2016
DOI: 10.1136/bjsports-2016-096550
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from prospective cohort studies does not support current dietary fat guidelines: a systematic review and meta-analysis

Abstract: Epidemiological evidence to date found no significant difference in CHD mortality and total fat or saturated fat intake and thus does not support the present dietary fat guidelines. The evidence per se lacks generalisability for population-wide guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 45 publications
1
31
1
4
Order By: Relevance
“…Findings from two SRMAs of observational studies showed that high SFA intake was not significantly associated with risk of CVD mortality [6,47] and CHD [6] (see Figures 4B and 5B). However, one SRMA of observational studies found that a high SFA intake was significantly associated with lower risk of ischemic stroke (pooled RR = 0.89; 95%CI: 0.82-0.96) [50] (see Figure 5A).…”
Section: Fat Intakementioning
confidence: 97%
See 1 more Smart Citation
“…Findings from two SRMAs of observational studies showed that high SFA intake was not significantly associated with risk of CVD mortality [6,47] and CHD [6] (see Figures 4B and 5B). However, one SRMA of observational studies found that a high SFA intake was significantly associated with lower risk of ischemic stroke (pooled RR = 0.89; 95%CI: 0.82-0.96) [50] (see Figure 5A).…”
Section: Fat Intakementioning
confidence: 97%
“…Fat intake was classified as (1) total fat intake, (2) saturated fatty acid (SFA), (3) MUFA, (4) n-3 PUFA, (5) n-6 PUFA, and (6) trans fatty acid (TFA). For total fat intake, the results from SRMAs of observational studies found that a high total fat intake did not significantly increase risk of CVD mortality (pooled RRs ranging from 0.94 (95%CI: 0.74-1.18) to 1.04 (95%CI: 0.98-1.10)) [6,47] ( Figure 4C) and CHD (pooled RR = 0.93; 95%CI: 0.84-1.03) [6] ( Figure 5B). Evidence from SRMAs of RCTs also indicated that modification of the amount of total fat intake did not significantly decrease risk of all-cause mortality (pooled RRs ranging from 0.98 (95%CI: 0.86-1.12) to 0.99 (95%CI: 0.94-1.05)) [48,49] (Figure 4B), CVD mortality (pooled RRs ranging from 0.91 (95%CI: 0.77-1.07) to 1.00 (95%CI: 0.80-1.24)) [6,48,49], or CHD (pooled RR = 0.93 (95%CI: 0.84-1.04) [6] ( Figure 5C) in the general population.…”
Section: Fat Intakementioning
confidence: 99%
“…A previous study reported that high unsaturated fatty acid intake may promote oxidative stress and increase the risk of CHD [17]; further, increased intake of high-fat diet increases the risk of myocardial infarction [18]. However, the relationship remains controversial [19]; a positive association was found between frequent high-fat food consumption and CHD risk in the USA, but not in Europe or Asia [20]. This could be attributed to the different dietary patterns and social conditions, as well as ethnic differences.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, cardiovascular disease is the most common cause of death. CHD accounted for more than 53% of all CVD-related deaths in 2016, and CHD-related mortality rate increased by 19.0% from 2006 to 2016 [1]. As the prevalence of risk factors has been increasing, the mortality rate of CHD has increased by 40.1% during the same period, with CHD accounting for 17.8% of all deaths in China [2].…”
Section: Introductionmentioning
confidence: 99%
“…In der Argumentation gegen eine Low-Carb-Ernährung wird oft angeführt, dass beim Wegfall von Kohlenhydraten die Zufuhr von Fett und insbesondere von gesättigten Fettsäuren ansteigen könne, was man für schädlich halte. Doch mittlerweile gibt es gute Belege, dass die undi erenzierte Empfehlung, Fett zu sparen und auf gesättigte Fette zu verzichten, zum Zeitpunkt ihrer Einführung nicht evidenzbasiert war und auch durch die neuesten epidemiologischen Daten nicht unterstützt wird [20,21]. Dennoch hält sich das jahrzehntelange Dogma hartnäckig.…”
Section: Sind Gesättigte Fettsäuren Schädlich?unclassified